A Simple Combined Method for Vaginal Breech Presentation Delivery: A Retrospective Single Tertiary Center Comparison of Outcomes Across Two Generational Approaches (2007–2022) - Kouskouti, Christina; Horky, Alex; Hajda, Simon; Haide, Sergej; Kainer, Franz (Zeitschrift für Geburtshilfe und Neonatologie, 2025)
The management of breech presentation at term has been a subject of controversy in recent decades. The Term Breech Trial (TBT) in 2000 demonstrated a significant reduction in perinatal morbidity and mortality through planned cesarean delivery, leading to increased rates of cesarean breech deliveries. Subsequent publications questioned the TBT results, yet without a significant increase in vaginal breech deliveries. This decline in vaginal breech deliveries has raised concerns about the training of the new generation. Here we introduce an individualized approach with careful selection of appropriate candidates and the application of a simple 3-step method (Hold – Lever – Rotate) for vaginal breech delivery.We conducted a retrospective analysis of two distinct periods: 2007-2012 and 2013-2022 to compare approaches to vaginal breech deliveries. The vaginal breech delivery rate was 8% (n=65) from 2007 to 2012 and 10% (n=146) from 2013 to 2022. The success rate for planned vaginal breech deliveries decreased from 62% to 53%.Risk stratification and informed patient selection are pivotal in managing vaginal breech deliveries. The proposed 3-step algorithm (Hold – Lever – Rotate) provides a simple and efficient method for obstetricians and midwives to manage breech deliveries safely, even with limited training opportunities.
Keywords: Breech; vaginal delivery; obstetrics